(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the association between chronic ear infections and the prevalence of hearing loss in children. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Community Medicine & ENT of DHQ Hospital & MBBS Medical College, Mirpur AJK from 1st September 2023 to 30th March, 2024. Methods: Comprehensive audiometric assessments were performed to evaluate hearing loss. Data on infection duration, frequency, and treatment history were collected through caregiver interviews and medical records. Statistical analysis, including chi-square tests and logistic regression, was used to determine the association between chronic ear infections and hearing loss. Results: Of 300 children, 45% (n=135) exhibited some degree of hearing loss. Conductive hearing loss was by far the most common type (79%, p<0.001), followed by mixed hearing loss (13%, p=0.02). Children with infection durations longer than six months were significantly more likely to experience hearing loss (OR=3.2; 95% CI: 2.2–4.6). Frequent infections (≥3 episodes per year) were also strongly associated with increased risk (OR=2.6; 95% CI: 1.7–4.3). Early diagnosis and timely treatment significantly reduced the likelihood of hearing loss (p=0.01). Conclusion: Chronic ear infections are strongly associated with hearing loss among children in Mirpur, AJK. These findings underscore the need for early intervention, routine hearing screenings, and public health initiatives to manage and prevent chronic ear infections effectively